The Analysis of Microstructure and the Properties of the Metallic-Matrix Composite on the Basis of the Copper and Aluminum Oxide; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Ivashutenko A. S. Alexander Sergeevich; Martyushev N. V. Nikita Vladimirovich; Vodopyanov E. M.; Bezborodov V. P. Valeriy Pavlovich (Materials Science in Mechanical Engineering, 2015)
Title screen